Will on the inside - Eliopulos, Andrew (New York, NY : Quill Tree Books, 2023)
After dedicated soccer player Will is sidelined from the season--and his friend group--due to complications from his newly diagnosed Crohn's disease, he finds himself figuring out who he really is on the inside.
School Library Journal starred, June 2023
Pub Weekly, May 2023
4.9
5-8
Keywords: Middle school boys -- Juvenile fiction; Crohn's disease -- Patients -- Juvenile fiction; Gay teenagers -- Juvenile fiction; Friendship -- Juvenile fiction; Middle school boys -- Fiction; Crohn's disease -- Patients -- Fiction; Gay teenagers -- Fiction; Friendship -- Fiction; Coming of age -- Fiction; Bildungsromans; LGBTQ+ fiction; Realistic fiction